If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + 8 = 14 Reorder the terms: 8 + 3z = 14 Solving 8 + 3z = 14 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 3z = 14 + -8 Combine like terms: 8 + -8 = 0 0 + 3z = 14 + -8 3z = 14 + -8 Combine like terms: 14 + -8 = 6 3z = 6 Divide each side by '3'. z = 2 Simplifying z = 2
| 37=X(0.965)/0.09 | | 7=2d+1 | | 23y/12=y/6-8 | | x^2=1500000 | | 23y=2y-8 | | 15mn-20n/5n | | x*(2/3)*x=1000000 | | 2x^2-13x+2= | | 24x^2=1000000 | | 1b+3c+x=1a+6e | | (3x-1)/4=2x-3 | | (3x-11)/4=2x-4 | | x^2-6=6x-6 | | 6(4x-5)=5 | | p(6)=10!/6!(10-6)! | | 8x+5x+2x+8=10x+4+2x | | 40X+20(200-X)=5600 | | 40X+20Y(200-X)=5600 | | Dy/dx=senx5x | | 13x+3y=50 | | y^2+3y+8=-2y+4 | | 5=4a+7a-3b | | (2x+6)+(5x-12)=99 | | x-1/3-x-1/2=5/4 | | (5x+1)(x-3)=(x-5)(5x-2)+2 | | 3(k-1)=k+6 | | y=50x+4 | | 4-5y=7-2(y-6) | | p=18-(2-3p) | | 49s-26=107 | | 6x-(5+2x)+5=x | | 5(p-1)=p+5 |